Biomimetic proteolipid vesicles for reverting GPI deficiency in paroxysmal nocturnal hemoglobinuria - Valentina Giudice; Pasqualina Scala; Erwin P. Lamparelli; Marisa Gorrese; Bianca Serio; Angela Bertolini; Francesca Picone; Giovanna Della Porta; Carmine Selleri (iScience, 2024)
Summary: Nano-vesicular carriers are promising tissue-specific drug delivery platforms. Here, biomimetic proteolipid vesicles (BPLVs) were used for delivery of glycosylphosphatidylinositol (GPI)-anchored proteins to GPI deficient paroxysmal nocturnal hemoglobinuria (PNH) cells. BPLVs were assembled as single unilamellar monodispersed (polydispersity index, 0.1) negatively charged (ζ-potential, −28.6 ± 5.6 mV) system using microfluidic technique equipped with Y-shaped chip. GPI-anchored and not-GPI proteins on BPLV surface were detected by flow cytometry. Peripheral blood mononuclear cells (PBMCs) from healthy and PNH subjects were treated with BPLVs (final concentration, 0.5 mg/mL), and cells displayed an excellent protein uptake, documented by flow cytometry immunophenotyping and confocal microscopy. BPLV-treated cells stressed with complement components showed an increased resistance to complement-mediated lysis, both healthy and PNH PBMCs. In conclusion, BPLVs could be effective nanocarriers for protein transfer to targeted cells to revert protein deficiency, like in PNH disease. However, further in vivo studies are required to validate our preclinical in vitro results.